The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1029/2018tc005079
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric Alteration, Intraplate Crustal Deformation, and Topography in Eastern China

Abstract: Topography can be directly observed, but what controls topographic variation is not readily known. To investigate a prominent and remarkably consistent along‐trend topographic gradient belt (TGB) in intraplate eastern China and its connection to ongoing deformation and geodynamics, we examine the regional density structure of the crust and mantle lithosphere. We first use S velocities to derive an initial density and then refine the density model by joint inversion of topography and gravity. We use the final d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…Our findings of high  Δ p t provide another line of evidence to support the idea that easternmost China as a whole has undergone lithospheric dismemberment (Y. Deng & Levandowski, 2018;Q. Wang et al, 2017;T.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our findings of high  Δ p t provide another line of evidence to support the idea that easternmost China as a whole has undergone lithospheric dismemberment (Y. Deng & Levandowski, 2018;Q. Wang et al, 2017;T.…”
Section: Discussionsupporting
confidence: 81%
“…No matter the inverse approach, a pronounced negative Flexural isostatic LAB (Deng and Levandowski, 2018) Seismic LAB (Zhang et al, 2018a) Thermal LAB (Deng and Tesauro, 2016) ∼200 km to 400 km and attributed these anomalies to delaminated lithosphere from the SE Tibetan Plateau. Fu et al, (2017) observed high S-wave velocity from Moho depths to 150 km based on Rayleigh wave tomography over the ChinArray-I project.…”
Section: The Sichuan Basin and Chuandian Fragmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The receiver function results implied a lithosphere thickness of ~65 km in southeast China [11,31]. Deng and Levandowski proposed that the depth of the lithosphere-asthenosphere boundary (LAB) is ranging around 100 km, which is estimated by the final density model and receiver functions [12]. A joint inversion of Rayleigh wave dispersion data, topography, geoid height, and terrestrial heat flow with a probabilistic Monte Carlo method predicts the recent lithosphere in South China is ranging from 80-105 km [10].…”
Section: Interpretations Of the Modelmentioning
confidence: 99%
“…These granites, Late Mesozoic granite, in particular, were formed by the remelting of the Neoproterozoic and Paleozoic crust [7] and extremely rich heat-producing elements (Th, U, and K) with average heat production of more than 5 µW/m 3 [8]. Second, various geophysical methods have led to the thin lithosphere (~80 km) present in South China [9][10][11][12]. Combining with studies on mantle peridotite enclaves/xenoliths in Paleozoic suggested that a lithospheric thinning process has occurred in Meso-Cenozoic [13][14][15].…”
Section: Introductionmentioning
confidence: 99%